Cellular Senescence as the Pathogenic Hub of Diabetes-Related Wound Chronicity - Berlanga-Acosta, Jorge A.; Guillén-Nieto, Gerardo E.; Rodríguez-Rodríguez, Nadia; Mendoza-Mari, Yssel; Bringas-Vega, Maria Luisa; Berlanga-Saez, Jorge O.; García del Barco Herrera, Diana; Martinez-Jimenez, Indira; Hernandez-Gutierrez, Sandra; Valdés-Sosa, Pedro A. (Frontiers in Endocrinology, 2020)
Diabetes is the only non-communicable disease with pandemic magnitude. Essentially defined as an endocrine-metabolic condition, its entangled pathophysiology and the broad spectrum of its ever progressing complications has turned this disease an intense investigational target that bridges to cancer, neurodegenerative processes, and ultimately to aging. Diabetic environment contains major stressors for the onset of premature cellular senescence and precocious organismal aging. Thus, diabetic subjects exhibit reduced tissue resilience and limited biological reserves for safeguarding mechanisms and injury counteraction. The impaired wound healing response is an illustrative example accounting for the majority of lower limbs amputations and reduced life expectancy. Classic studies seeded the notion that cellular senescence is a founding pillar for the orchestration of the chronic phenotype of diabetic wounds. Tracking the diabetes molecular senescence drivers teach that glucose and its derivative glucooxidative products act as a chain reaction within progressive vicious circle in which the classic “aging hallmarks” are pathogenically instrumental. Mitochondrial dysfunction and the interconnected dysmetabolism, the onset of a pro-oxidative milieu, and an inflammatory activation program, conspire against DNA integrity, which ultimately triggers the molecular switches for a cellular senescence program. Fibroblasts, endothelial cells and keratinocytes are chronically exposed to major organismal stressors that catalyze their premature aging. These in-wound senescent cells create a society via a senescence secretome that, in a paracrine manner, contributes to society perpetuation and wound chronicity. The senescence phenotype memory turns these cells refractory to migrate, proliferate, and secrete granulation tissue ingredients under in vivo and in vitro scenarios. Mesenchymal stem cells are also impacted by the diabetes-related pro-senescence forces, which may translate in a reduction of the natural reservoir of competent cells for wound repair, tissue turnover, and ultimately to organismal conservation.